Investigations of the thermo-mechanical stability of hybrid layers for tribological applications: Nitrided layer/CrCN coating system. (February 2018) - Myśliński, Piotr; Szparaga, Łukasz; Gilewicz, Adam; Mydłowska, Katarzyna; Piątkowska, Anna
Abstract: The paper contains a description of investigations related to an analysis of thermo-mechanical couplings in nitrided and non-nitrided steel substrate/CrCN coating systems with the use of dilatometry with temperature modulation. In this method, measured quantities are changes in the linear elongation of substrates in layered systems that occur as a result of given thermal loads. This enable i.a. to assess thermally activated changes in the states of residual stresses in the system as a result of a number of physical and chemical processes in the coating and in the substrate. Independently, results of these investigations were confronted with the results of scratch test enabling the assessment of coating adhesion and fracture toughness. On the grounds of the investigations carried out, it was found that CrCN coatings deposited on the nitrided substrates demonstrate a stronger thermo-mechanical coupling with the substrate in comparison with coatings deposited on the non-nitrided substrate and are characterized by a higher thermal stability. The results obtained explicitly confirm that systems with nitrided substrates are characterized by a higher mechanical load-bearing capacity and more favorable state of the adhesion of the coating to the substrate is observed as compared to systems with non-nitrided substrates. Highlights: Nitriding of steel substrates enhances thermal stability of PVD coating/substrate systems. Strong thermo-mechanical coupling for nitrided substrates and CrCN coatings was shown. Improvement in adhesion state was achieved using nitrided substrates. Critical forces change least after annealing for coatings on nitrided substrates.